Contribution of satellite sea surface salinity to the estimation of liquid freshwater content in the Beaufort Sea - Umbert, Marta; De Andrés, Eva; Sánchez, Maria; Gabarró, Carolina; González-Gambau, Veronica; García, Aina; Olmedo, Estrella; Raj, Roshin P.; Xie, Jiping; Catany, Rafael (Copernicus Publications, 2023)
The hydrography of the Arctic Ocean has experienced profound changes over the last two decades. The sea-ice extent has declined more than 10 % per decade, and its liquid freshwater content has increased mainly due to glaciers and sea ice melting. Further, new satellite retrievals of Sea Surface Salinity in the Arctic might contribute to better characterizing the freshwater changes in cold regions. That is because ocean salinity and freshwater content are intimately related such that an increase/decrease of one entails a decrease/increase of the other. In this work we evaluate the freshwater content in the Beaufort Gyre, using surface salinity measurements from the satellite radiometric mission Soil Moisture and Ocean Salinity (SMOS) and reanalysis salinity at depth. We estimate the freshwater content from 2011 to 2019 in the Beaufort Gyre and validate the results with in-situ measurements. The results highlight the underestimation of the freshwater content using reanalysis data in the Beaufort Sea and a clear improvement in the freshwater content estimation when adding satellite sea surface salinity measurements above the mixed layer. The improvements are significant, especially in areas close to ice melting. Our research demonstrates how remotely sensed salinity can assist us in better monitoring the changes in the Arctic freshwater content and improving our understanding of a key process that is creating subtle density differences that have the potential to change the global circulation system that regulates Earth’s Climate.